Schema Therapy in Adolescents with Disruptive Behavior Disorders. Issue 3 (3rd July 2017) - Van Wijk-Herbrink, Marjolein F.; Broers, Nick J.; Roelofs, Jeffrey; Bernstein, David P.
ABSTRACT: This multiple case study examined the feasibility and effectiveness of an innovative residential treatment, based on Schema Therapy (ST), for adolescents with disruptive behaviors and Personality Disorder (PD) traits. We reported case narratives as well as quantitative changes in behavior problems, early maladaptive schemas, and schema modes of four patients. In terms of feasibility, the therapist was able to use the full range of ST techniques (working in the here and now, experiential techniques, and cognitive-behavioral techniques) with all four patients. We trained and coached treatment teams in ST theory and practice, and were partially successful in involving patients' parents in the ST treatment. Qualitative and quantitative findings showed that patients improved in their behavior problems, early maladaptive schemas, and schema modes. These results support the feasibility of ST for adolescents with disruptive behaviors and PD traits in residential treatment, and provide preliminary evidence of its effectiveness.